Under box 36x + 9, Drag the following:
A.) 9(4x + 1)
D.) (9 . 4x) + (9 . 1)
Under box 9(4x - 1), Drag the following:
B.) (3 . 12x) - (3 . 3)
C.) 36x - 9
Under box (4 . 9x) + (4 . 2), Drag the following:
E.) 4(9x + 2)
F.) 36x + 8
Hope this helps!
x² + 10x = 26
x² + 10x + 25 = 26 + 25
x² + 5x + 5x + 25 = 51
x(x) + x(5) + 5(x) + 5(5) = 51
x(x + 5) + 5(x + 5) = 51
(x + 5)(x + 5) = 51
(x + 5)² = 51
x + 5 = ±√(51)
- 5 - 5
x = -5 ± √(51)
x = -5 + √(51) or x = -5 - √(51)
10 9/10.... because 10 can be divided into 109 10 whole times with a remainder of 9 so you put the 9 over the original denominator which is 10 so 9 over 10
Answer:
A, C, and D
Step-by-step explanation: